KETERKAITAN KINERJA PEGAWAI DENGAN BUDAYA ORGANISASI, KEPUASAN KERJA DAN KOMPETENSI DITINJAU DARI STATUS KEANGGOTAAN PEGAWAI DI AKADEMI ANGKATAN UDARA YOGYAKARTA TAHUN 2014 (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
The aim of this study were: (1) To determine the influence of organizational culture, job satisfaction and competence together on employee performance AAU Yogyakarta in 2014; (2) To determine the influence of organizational culture on employee performance AAU Yogyakarta in 2014; (3) To determine the effect of job satisfaction on employee performance AAU Yogyakarta in 2014; (4) To determine the effect on the performance of employee competence AAU Yogyakarta in 2014; and (5) To determine the performance of civil servants and employees AAU Yogyakarta Yogyakarta AAU members of the military in 2014. Research conducted at the AAU Yogyakarta on July 1 until August 1, 2014. The variables in this study are organizational culture, job satisfaction, competence and performance of employees. The population in this study were all employees of Employees AAU Yogyakarta totaling 538 people. The amount of sample is 208 people, with details of 104 military personnel and 104 civil servants. The sampling technique used is random sampling. The technique of collecting data using questionnaires. The analysis used is multiple regression analysis. Based on the results of the study concluded that: 1) organizational culture, job satisfaction and competence positive and significant impact on employee performance AAU Yogyakarta in 2014 amounted to 37.58%; thus the better the organizational culture, job satisfaction and competence of the employee's performance is increasing AAU Yogyakarta. (2) Organizational culture positive and significant impact on employee performance AAU Yogyakarta in 2014 amounted to 8.26%; thus the better the culture of the organization, the AAU Yogyakarta employee performance will increase. (3) Job satisfaction and significant positive effect on employee performance AAU Yogyakarta in 2014 amounted to 15.96%; thus the better the job satisfaction of the employee's performance will increase AAU Yogyakarta. (4) Competence positive and significant impact on employee performance AAU Yogyakarta in 2014 amounted to 13.35%; thus the better the competence of the employee's performance is increasing AAU Yogyakarta. (5) There is a significant difference in the performance of civil servants AAU Yogyakarta (70.62) and TNI members AAU Yogyakarta (66.86) in 2014. Thus, the performance of civil servants AAU Yogyakarta higher than the performance of military members AAU Yogyakarta.